LA IMAGEN DE UNIÓN EUROPEA Y DE SUS PAÍSES MIEMBROS EN LA PRENSA OFICIAL CHINA XINHUA ONLINE: UN ESTUDIO EMPÍRICO - Lifen CHENG,Potseng CHEN,Shiany PÉREZ-CHENG (Fonseca, Journal of Communication, 2023)
This study analyzes the portrayals of European Union and its member countries depicted by the Chinese media. It aims to explore the news content from a different angle by shifting the usual western perspective to a Chinese approach